The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1980-4415v31n58a15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by Experts and Designated Users on the Learning Strategy using SketchUp Make for Elevating Visual Spatial Skills and Geometry Thinking

Abstract: The teaching and learning of Geometry should be meaningful and not merely reacting to the teacher's stimuli. Hence, students should be given opportunities to experiment when learning mathematics through exploration and investigation of geometric shapes by themselves. For that reason, a Learning Strategy for 3-dimensional Geometry using the SketchUp Make dynamic software, called LSPE-SUM was designed through a step-by-step instruction to help students to improve their visual spatial skills and geometric thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…Therefore, this study attempt was made to determine the validity of the developed learning strategy called VH-iSTEM which was develop based on the connections between the iSTEM approach (engineering design phases) and van Hiele phases of learning geometry before its effectiveness was determined in the implementation stage. More so, to ensure the achievement of module objective as well as the activities provided in the learning strategy a pre-test and post-test were conducted as suggested Meyer in [34].…”
Section: Statements Of the Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study attempt was made to determine the validity of the developed learning strategy called VH-iSTEM which was develop based on the connections between the iSTEM approach (engineering design phases) and van Hiele phases of learning geometry before its effectiveness was determined in the implementation stage. More so, to ensure the achievement of module objective as well as the activities provided in the learning strategy a pre-test and post-test were conducted as suggested Meyer in [34].…”
Section: Statements Of the Problemsmentioning
confidence: 99%
“…To gain the validity of a module Meryer in Wahab et al [34], suggested the conduct of simple analysis to determine the quality and effectiveness of activity develop in learning strategy. To achieve this, evaluation forms were provided to experts to rate the content, based on its objectives, sufficiency, students-center, the integration of STEM with strategy, and also based on lesson activity organization that covers, connections between iSTEM and van Hiele phases of learning geometry; collaborative and independent learning on the activities, orderliness in the connection of the phases in VH-iSTEM learning strategy.…”
Section: A Research Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in achievement in Geometry as shown in the Trends in International Mathematics and Science Study (TIMSS) assessment was a 'wakeup call' to Malaysians educators, generally and specifically. It was reported by Mullis et al (2012) that only 33% of Malaysian students could answer Geometry questions successfully. The achievement rate in the cognitive Geometry domain was 53% at knowledge and 28% at reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed by Mullis et al (2012), the current approaches and teaching methods in the classrooms were still confined to the traditional teacher-centered approach. Similar findings were also reported by Noraini (2006) and Abdul Halim and Effandi (2013) who found that teachers' Geometry learning activities were uncreative and boring due to merely using blackboard to explain definitions, concepts, and specific theorems.…”
Section: Introductionmentioning
confidence: 99%